Gambaran Self Efficacy Pada Mahasiswa di Kota Bandung Terhadap Penyelesaian Skripsi di Era Hybrid Learning - Anisya Divani; Favian Hawari; Muhammad Rafi; Nurriska Khairunisya; Salsabila Anisa Riyanto; Sufia Dwi Ambarini (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2022)
Hybrid learning is a learning method that is carried out in two ways, namely face to face and distance. The use of these different methods can affect the way students behave, one of which is the student who composes the thesis. In this case, students are required to be able to make their own decisions and be confident in their own abilities so that their thesis can run well and smoothly, therefore it is necessary to categorize the self-efficacy of final students who are preparing a thesis. thesis. The method used in this research is descriptive quantitative method. The results of this study indicate that students who are writing thesis have low self-efficacy scores (05%), moderate (29.2%) and high (70.3%).